Pengaruh Kedisiplinan Belajar dan Iklim Komunikasi Terhadap Hasil Belajar Produktif Persamaan Dasar Akuntansi Pada Siswa Kelas X Jurusan Akuntansi SMK Negeri 6 Makassar - Sitti Fatimah Azzahra B; M. Ridwan Tikollah; Sitti Hajerah Hasyim (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2026)
This study aims to analyze the influence of learning discipline and communication climate on the productive learning outcomes of basic accounting equations in class X accounting students at SMK Negeri 6 Makassar. A saturated sample was used in this study with 97 students as respondents. Data were collected using a questionnaire survey to the students. The results show that the communication climate has a partial effect on the productive learning outcomes of basic accounting equations. Learning discipline and communication climate have a simultaneous effect on the productive learning outcomes of basic accounting equations. Learning discipline has a dominant effect on the productive learning outcomes of basic accounting equations.